Protein Digestibility of Trembesi Leaf Fermented with Lactobacillus plantarum AK-3 - Ahimsa Kandi Sariri; Ali Mursyid Wahyu Mulyono (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2020)
This study aims to assess the digestibility of trembesi leaf protein fermented with Lactobacillus plantarum AK-3. Trembesi leaves are fermented by adding Lactobacillus plantarum AK 3 which is isolated from cow's milk waste. Then the protein digestibility was analyzed for ruminants. This research is descriptive so the data obtained is descriptive data about the level of digestibility of crude protein from fermented leaves. The conclusion obtained is the level of crude protein digestibility of the leaves of fermented trembesi Lactobacillus plantarum AK-3 by 71%.Key word: fermentation, trembesi leaf, protein digestibility, Lactobacillus plantarum AK-3